Pengembangan Karakter Akhlaqul Karimah di Kalangan Santri Pondok Pesantren Tahfidzul Qur'an - Mutiara Amanda Angelita (Jurnal Pendidikan Nusantara, 2023)
The development of the character of Akhlaqul Karimah among students at the Tahfidzul Qur'an Aisyiyah Islamic Boarding School, Ponorogo, an Islamic boarding school is described in this research. The formation of strong character, noble character, and the ability to internalize religious values is the main focus in Islamic education. This research uses a qualitative approach, with observation and in-depth interviews as the main tools. Research shows that religious education plays an important role in forming the character of Akhlaqul Karimah. The role of educators, social interactions between students, and the Islamic boarding school environment also influence character development. Santri who truly understand the values of Akhlaqul Karimah tend to participate more actively in character development. Pressure from the environment outside the Islamic boarding school and technological interference are other challenges in character formation. Nevertheless, Islamic boarding schools continue to have an important role in building character with good morals. This research provides in-depth insight into the process of developing the character of Akhlaqul Karimah among students at the Tahfidzul Qur'an Islamic Boarding School Aisyiyah Ponorogo and underlines the importance of religious education, the role of educators, and the Islamic boarding school environment in forming characters with noble morals. By further understanding the factors that influence character development, it is hoped that we can design more effective educational strategies to form a young generation who have good morals and are able to make positive contributions to society.